Service characteristics of biomedical materials and implants - Batchelor, A. W. (Andrew W.) (Series on biomaterials and bioengineering ;, 2004)
"This book collates information and provides a concise text on the performance of different materials used in devices and implants. The knowledge presented is critical for a biomedical engineer, especially for the purpose of selecting the right materials. In addition, topics such as allergies and infection, tissue scaffolds, and drug delivery are reviewed."--Jacket